Parables in changing contexts : essays on the study of parables in Christianity, Judaism, Islam, and Buddhism - Ottenheijm, Eric, 1961-; Poorthuis, Marcel, 1955- (Jewish and Christian Perspectives Series;, 2020)
"In Parables in Changing Contexts, new venues in the comparative study of parables are addressed by scholars of Judaism, New Testament, Buddhism and Islam. Essays cover parables in the synoptic Gospels, Rabbinic midrash, and parabolic tales and fables in the Babylonian Talmud. Three essays address parables in Islam and Buddhism. The volume shows how parables are suitably adapted in terms of form and rhetoric to enhance religious identity formation. Parables serve as media, as sensational forms making the sacred present, albeit encoded or riddled, in all cases invoking the listener's active interpretative participation and cultural imagination. Adapting a multidisciplinary approach to these gems of storytelling, parables in a particular way provide new insights in the cultures that produced them".